The Effect of Mindfulness Intervention (MPSE) on Motivation and Burnout in Athletes - Fereshteh Golestaneh (University of Tehran, 2017)
During recent years, mindfulness interventions have shown significant effects on athletic performance; however, researches on the effectiveness of these interventions on important psychological characteristics such as motivation and burnout of athletes are limited. The aim of this study was to investigate the effect of sports mindfulness intervention (MPSE) on motivation and burnout in athletes. For this purpose, 40 athletic students of Chabahar University were selected as the sample by convenience sampling method and were divided into intervention and control groups. Exercise Motivation Questionnaire (SMS-6) and Sports Burnout Questionnaire (ABQ) were used to collect data. 6 weeks of sport mindfulness intervention were used for athletes. Questionnaires were distributed among athletes before and after the intervention and data from questionnaires were analyzed by SPSS software version 20 by means of descriptive and inferential statistics (analysis of covariance). The results showed that sport mindfulness intervention significantly decreased the burnout (P>0.05). These interventions also significantly increased intrinsic motivation and significantly decreased demotivation and extrinsic motivation of athletes (P<0.05). These results suggested that sport mindfulness interventions can be used as an appropriate instrument to increase the autonomy of sport motivation and to reduce the harmful effects of sport burnout.